2010
DOI: 10.1111/j.1939-0025.2010.01049.x
|View full text |Cite
|
Sign up to set email alerts
|

A dual‐factor model of mental health: Toward a more comprehensive understanding of youth functioning.

Abstract: Traditional mental health models focus on psychological problems and distress; accordingly, health is viewed as the absence of illness or disability. In contrast, a dual-factor model of mental health incorporates both indicators of positive subjective well-being (SWB) and measures of psychopathological symptoms to comprehensively determine an individual's psychological adjustment. This study used such a dual-factor model to measure the mental health status of young adolescents. A total of 764 middle school stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
281
1
14

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 319 publications
(312 citation statements)
references
References 33 publications
16
281
1
14
Order By: Relevance
“…For example, Westerhof and Keyes (2010) found in a study of Dutch adults that older adults had fewer mental illness problems than younger adults but did not have better positive mental health. Some similar research has also been undertaken with children (Antaramian et al 2010;Suldo and Shaffer 2008) although here, also, longitudinal evidence is lacking.…”
Section: The Distinction Between Positive Mental Health and Mental Ilmentioning
confidence: 99%
“…For example, Westerhof and Keyes (2010) found in a study of Dutch adults that older adults had fewer mental illness problems than younger adults but did not have better positive mental health. Some similar research has also been undertaken with children (Antaramian et al 2010;Suldo and Shaffer 2008) although here, also, longitudinal evidence is lacking.…”
Section: The Distinction Between Positive Mental Health and Mental Ilmentioning
confidence: 99%
“…Although the DFM does not focus on the evaluation of strengths, it paves the way for strengthbased assessments [19]. According to DFM, specific fundamental individual characteristics, such as personality, may substantially influence children's mental health status [6]. These point out the direction for "predicting mental health based on psychological suzhi" or "fostering psychological suzhi to promote and substantially maintain mental health" [14]; and reflect the thought that psychological suzhi should be included in the model to develop relationship model between psychological suzhi and mental health.…”
Section: Preliminary Development Of Relationship Model Between Psychomentioning
confidence: 99%
“…It can be used to classify people into complete mental health, incomplete mental health, incomplete mental illness and complete mental illness four groups based on such indicators and to forecast the mental health functions of those four groups and the development trend of their mental health [1,3,6,7].…”
Section: It Classifies the Mentally Healthy Peoplementioning
confidence: 99%
See 1 more Smart Citation
“…Extant research has shown how affect and wellbeing are closely related to school engagement and achievement (Reschly, Huebner, Appleton, & Antaramian, 2008). Students who have a past negative time perspective are more likely to experience negative affect which has been shown to be detrimental to school functioning (Antaramian, Huebner, Hills, & Valois, 2010).…”
Section: Figurementioning
confidence: 99%